2017
DOI: 10.1002/lary.26888
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexmedetomidine for perioperative morbidities in pediatric tonsillectomy: A metaanalysis

Abstract: Perioperative administration of dexmedetomidine can provide pain and agitation relief without side effects in children undergoing adenotonsillectomy. Considering the high heterogeneity of results within some parameters; however, further clinical trials with robust research methodology should be conducted to confirm the results of this study. Laryngoscope, 128:E184-E193, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
4
20
0
Order By: Relevance
“…Adenotonsillectomy is one of the most commonly performed surgical procedures in childhood. However, the post‐operative period is exhausting for patients, and many suffer from post‐operative pain and agitation . Pain is more commonly felt during recovery after anaesthesia and may lead to reduced oral intake, dehydration and agitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adenotonsillectomy is one of the most commonly performed surgical procedures in childhood. However, the post‐operative period is exhausting for patients, and many suffer from post‐operative pain and agitation . Pain is more commonly felt during recovery after anaesthesia and may lead to reduced oral intake, dehydration and agitation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta‐analysis, the effects of perioperative dexmedetomidine used an adjuvant during an adenotonsillectomy was compared with the use of opioid or placebo in paediatric patients who underwent adenotonsillectomy surgery . It was found that dexmedetomidine significantly lowered post‐operative pain and the need for analgesic drugs compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared to propofol sedation it also has been shown to be associated with lower rates of delirium [40]. In children dexmedetomidine significantly reduced delirium and agitation in the PACU stage following tonsillectomy [41,42]. This effect is probably due to its opioid sparing properties because opioids are one of the main precipitants of post-operative confusion states.…”
Section: Gastrointestinal Actionsmentioning
confidence: 99%